2010
DOI: 10.1088/2041-8205/725/2/l200
|View full text |Cite
|
Sign up to set email alerts
|

A Ground-Based Measurement of the Relativistic Beaming Effect in a Detached Double White Dwarf Binary

Abstract: We report on the first ground-based measurement of the relativistic beaming effect (aka Doppler boosting). We observed the beaming effect in the detached, non-interacting eclipsing double white dwarf (WD) binary NLTT 11748. Our observations were motivated by the system's high mass ratio and low luminosity ratio, leading to a large beaming-induced variability amplitude at the orbital period of 5.6 hr. We observed the system during 3 nights at the 2.0m Faulkes Telescope North with the SDSS-g ′ filter, and fitted… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 20 publications
3
72
2
Order By: Relevance
“…It was predicted to be seen in Kepler data by Loeb & Gaudi (2003) and Zucker et al (2007), and has recently been observed in several systems from ground-based data as well as Kepler and CoRoT light curves (see e.g. Mazeh & Faigler 2010;van Kerkwijk et al 2010;Shporer et al 2010;Bloemen et al 2011). Based on the radial velocity measurements of the primary star (semi-amplitude, K = 11.78 kms −1 -see Table 3), we estimate that Doppler beaming should have a significant contribution in the light from the red giant in KIC 5006817, of the order of ∼300 ppm.…”
Section: The Puzzling Absence Of a Doppler Beaming Signalmentioning
confidence: 56%
“…It was predicted to be seen in Kepler data by Loeb & Gaudi (2003) and Zucker et al (2007), and has recently been observed in several systems from ground-based data as well as Kepler and CoRoT light curves (see e.g. Mazeh & Faigler 2010;van Kerkwijk et al 2010;Shporer et al 2010;Bloemen et al 2011). Based on the radial velocity measurements of the primary star (semi-amplitude, K = 11.78 kms −1 -see Table 3), we estimate that Doppler beaming should have a significant contribution in the light from the red giant in KIC 5006817, of the order of ∼300 ppm.…”
Section: The Puzzling Absence Of a Doppler Beaming Signalmentioning
confidence: 56%
“…Given the short duration of the eclipse (≈3 minutes), any remaining variations in the relative photometry due to transparency or airmass changes could be ignored; we did not attempt to model the out-of-eclipse data (cf. Shporer et al 2010). …”
Section: Ultracam Observationsmentioning
confidence: 99%
“…The pulsational properties of ELM WDs have been explored theoretically by Van Grootel et al (2013) and Córsico & Althaus (2014, 2016. The DA WD instability strip is both empirically and theoretically found to shift to lower T eff with lower log g, intersecting the population of sdAs Shporer et al 2010;Kilic et al 2011b;Hermes et al 2014). In the case of the 12.75-minute binary SDSS J0651+2844, these have enabled the measurement of orbital decay from gravitational radiation (Hermes et al 2012b).…”
Section: Introductionmentioning
confidence: 99%